Rapid KL / Nur Fatihah Mohd Shah, Nurul Izzati Zafirah Zulfikri and Raihan Batrisyia Ramli - Mohd Shah, Nur Fatihah; Zulfikri, Nurul Izzati Zafirah; Ramli, Raihan Batrisyia (2018)
As we all know, that transportation is a vital thing in this modern era to enable us to travel and go to various places and continue our life routine perfectly. There are various types of transportations that have already invented for our convenience and one of the most popular transportation is bus. Rangkaian Pengangkutan Integrasi Deras Sdn Bhd or also known as RapidKL is one of the biggest public transportation services in Malaysia providing good service and low price fare. Rapid KL consists of two types of operators which are Rapid Rail Sdn Bhd and Rapid Bus Sdn Berhad, providing a different types of transportation; Light Rail Transit (LRT), Mass Rapid Transit (MRT), monorail, Bus Rapid Transit (BRT) and bus.